Typification of two Linnaean names: Centaurea aspera and Centaurea isnardii (Asteraceae) - Ferrer-Gallego, Pedro Pablo; Roselló, Roberto; Laguna, Emilio; Gómez, José; Peris, Juan B. (Phytotaxa, 2014)
The typification of the names Centaurea aspera L. and C. isnardii L. (Asteraceae) is discussed. A lectotype for C. aspera is designated from original material conserved in UPS-BURSER (Joachim Burser Herbarium). Centaurea isnardii is typified by an illustration of Isnard (1719) confirming this name as a synonym of C. aspera subsp. aspera.